2020
DOI: 10.3390/ijms21207516
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Cypridina Luciferin in the Presence of Human Plasma Alpha 1-Acid Glycoprotein

Abstract: The enzyme Cypridina luciferase (CLase) enables Cypridina luciferin to emit light efficiently through an oxidation reaction. The catalytic mechanism on the substrate of CLase has been studied, but the details remain to be clarified. Here, we examined the luminescence of Cypridina luciferin in the presence of several proteins with drug-binding ability. Luminescence measurements showed that the mixture of human plasma alpha 1-acid glycoprotein (hAGP) and Cypridina luciferin produced light. The total value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Several relevant findings were reported for vargulin -a substrate of Vargula/Cypridina luciferase -which has the same imidazopyrazinone core as CTZ. Its chemiluminescence was also shown to be enhanced by albumin and a few other binding proteins (Kanie et al, 2020). β-CD and its methylated derivatives increased the already relatively high chemiluminescence of MCLA (a vargulin analog), with 10 mM dimethyl-β-CD providing a 6-fold increase in luminescence (Mitani et al, 1995).…”
Section: It Erat Ure Backg Ro Und and Suppo Rt Ing Dat A L It Erat Ure Backg Ro Und And Suppo Rt Ing Dat Amentioning
confidence: 99%
“…Several relevant findings were reported for vargulin -a substrate of Vargula/Cypridina luciferase -which has the same imidazopyrazinone core as CTZ. Its chemiluminescence was also shown to be enhanced by albumin and a few other binding proteins (Kanie et al, 2020). β-CD and its methylated derivatives increased the already relatively high chemiluminescence of MCLA (a vargulin analog), with 10 mM dimethyl-β-CD providing a 6-fold increase in luminescence (Mitani et al, 1995).…”
Section: It Erat Ure Backg Ro Und and Suppo Rt Ing Dat A L It Erat Ure Backg Ro Und And Suppo Rt Ing Dat Amentioning
confidence: 99%
“…1 Although a luciferin typically emits light only in the presence of the corresponding luciferase, IPT luciferin often exhibits nonspecific luminescence reactions toward nonluciferase proteins or other biomolecules, as observed in both cellularand animal-imaging studies. 3 To date, some reports have revealed that nonluminescent proteins, such as serum proteins including human plasma alpha 1-acid glycoprotein, 4 bovine serum albumin, 3 and insulin, 5 can catalyze the nonspecific luminescence oxidative reaction of natural IPT luciferin, even though they have not been assigned an EC number and are not recognized as enzymes. We have recently demonstrated that CTZ derivative HuLumino1, which is an IPT luciferin with a side-chain chemical structure that is different from that of CTZ, is selectively recognized and enzymatically oxidized to exhibit light by one of several hydrophobic pockets (drug-binding site 2) in human serum albumin (HSA).…”
Section: ■ Introductionmentioning
confidence: 99%
“…12,13 Moreover, some studies have suggested that the luminescence reaction of IPT luciferin requires a hydrophobic pocket as an oxidative reaction field. 4,6,14 Therefore, we hypothesized that specific luminescence detection of the S protein could be achieved by selecting a luciferin that specifically fits into the hydrophobic pockets of the S protein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the most studied CL/BL substrates is Coelenterazine (Clz, Scheme 1 ) [ 1 , 3 , 16 , 17 , 18 , 19 , 20 , 21 ], which is present in many marine BL organisms [ 22 ]. Clz is capable of both BL (with luciferase enzymes or photoproteins) [ 3 ] and CL (triggered without an enzyme/protein by oxygenation) [ 23 , 24 , 25 ]. These Clz-based reactions follow a mechanism that consists in two steps: first, there is the oxygenation of the imidazopyrazinone core that leads to the formation of dioxetanone, the high-energy peroxide intermediate; the dioxetanone will undergo thermolysis almost instantly due to its high instability, during which the reacting molecules can cross directly to singlet excited states, resulting in the chemiexcited light emitter coelenteramide [ 1 , 3 , 4 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another example of natural CL/BL imidazopyrazinone compounds found in marine species is Cypridina luciferin (CypLuc, Scheme 1 ), which can be found in the ostracod Cypridina hilgendorfii [ 23 , 24 ]. Besides natural imidazopyrazinones, synthetic analogs have also been developed over the years, with some being already commercialized.…”
Section: Introductionmentioning
confidence: 99%